Better policy analysis with better data. Constructing a social accounting matrix from the European system of national accounts" - Santos, Susana (2009)
This paper will discuss the importance of the SAM (Social Accounting Matrix) as a consistent and flexible database for economic modelling to be used for the purpose of ensuring a better policy analysis. It will be shown how the SAM represents the circular flow of income and how it can support disaggregated economy-wide modelling. It will further be demonstrated how a SAM can be constructed from the SNA 93 (1993 version of the United Nations System of National Accounts) in an ESA 95 framework (European System of National and Regional Accounts in the European Community of 1995), and, using an example for Portugal, how it can be implemented in the European Union.